Kkn Sisdamas : Metode Efektif Membaca Al-Qur’an Di Desa Padaasih Dusun Ii Rw Viii (Studi Kasus Peran Pengabdian KKN Sisdamas di Desa. Padaasih Kec. Cisarua Kab. Bandung Barat) - Muhtadi, Ali; Syawal Sidik, Muhammad; Habibati Kusuma, Galih; Nisfanahari, Siti Sarah (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
Community service activities carried out in the community through attracting community participation to learn effective methods of reading the Quran. Because after conducting a survey to the community, It was found that there are still many children who cannot read the Quran according to their tajweed, and The children are still not fluent and still not in accordance with the reading with all the laws of the recitation of the Quran. The objectives of the activity are : Provide assistance to children who recite in the form of knowledge, energy or something useful. The method used in this program is teaching the science of tajweed and makhorijul letters, This KKN takes a program to teach about effective methods of learning the Quran so that children in the village can read the Quran properly and correctly in accordance with the science of tajweed and makhorijul letters are expected to be carried out in everyday life. This program is carried out in madrasah dusun two every afternoon or bada magrib. The results of this service show that children who used to not know the rules of the law of reading, makhrajul letters and tajweed in reading the Quran, after the implementation of the service of KKN sisdamas students in the community in this assistance made children more aware and able to practice the legal rules of reading the Quran correctly.